2005
DOI: 10.1080/15325020590908849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Previous Pregnancy Loss on Level of Maternal Anxiety After Prenatal Ultrasound Screening for Fetal Malformation

Abstract: The impact of previous stillbirth, miscarriage, or preterm delivery on anxiety in pregnant women in various subgroups at high risk for fetal abnormality in comparison with a nonrisk control group of women with healthy uncomplicated pregnancies was studied longitudinally. The level of anxiety in women (n ¼ 674) during early pregnancy was assessed by questionnaire. Data were collected at three points in time: immediately before the ultrasound scanning, at 5-6 weeks, and at 10-12 weeks after the prenatal examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
4
0
2
Order By: Relevance
“…The lower heterogeneity in the pregnancyspecific anxiety analysis may suggest that this provides a better model of anxiety in women during pregnancy following perinatal loss. However, some women may continue to have elevated anxiety levels after the first trimester and into the postpartum period (Brisch et al, 2005;Robertson Blackmore et al, 2011;Woods-Giscombe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The lower heterogeneity in the pregnancyspecific anxiety analysis may suggest that this provides a better model of anxiety in women during pregnancy following perinatal loss. However, some women may continue to have elevated anxiety levels after the first trimester and into the postpartum period (Brisch et al, 2005;Robertson Blackmore et al, 2011;Woods-Giscombe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…of an important pregnancy task, the protection of the fetus from harm. On the other hand, there is evidence which suggests too much anxiety can be harmful for the developing fetus by reducing blood fl ow to the uterus and increasing the fetal heart rate (Monk et al, 2003;Brisch et al, 2005).…”
Section: Tammy S Harpelmentioning
confidence: 99%
“…A recent study has shown the location of data collection had a significant impact on state anxiety scores; women who completed the STAI questionnaire in a “high-risk” hospital-based clinic had higher state anxiety scores in comparison to women approached at “low-risk”, community based clinics ( 28 ). A longitudinal study in Germany showed that women who had previously experienced still-birth and miscarriage had increasing levels of anxiety on the STAI questionnaire despite the obstetrician’s confirmation of good health of the foetus and normal development of the pregnancy ( 29 ).…”
Section: Discussionmentioning
confidence: 99%